Improving Fine Motor Skills Through Folding Activities Using Colored Paper Media for Group B Children of RA Perwanida Umbuldamar - Zamrodah, Erlis (DEEP LEARNING: Journal of Educational Research, 2025)
This study aims to improve fine motor skills through origami in children of Group B RA Perwanida Umbuldamar. This type of research is collaborative Classroom Action Research using the Kemmis and Mc Taggart model. The subjects of the study were 18 children in Group B consisting of 8 girls and 10 boys. The object of this study is fine motor skills. The data collection methods used are observation, documentation, and interviews. The instruments used are observation guidelines and interview guidelines. Data analysis techniques are carried out descriptively quantitatively and qualitatively. The success indicator set is if at least 75% of the 18 children have fine motor skills with good criteria. This study was conducted in two cycles. The results showed that children's fine motor skills increased after the action through paper folding. At the time of the pre-action observation, the percentage of children's fine motor skills was 26.07%. In Cycle I it was 49.00% with an increase of 22.93%, Cycle II it was 84.00% with an increase of 61.07% from cycle I, The percentage obtained shows that the fine motor skills of children in Group B with good criteria have achieved a success indicator of 75%. The steps taken to improve children's fine motor skills are 1) the teacher explains how to fold paper using the demonstration method; 2) children are given reinforcement with the words "iron folds" that have been made; 3) children are given rewards in the form of praise; 4) the use of patterned folding paper to attract children's interest.